On the sufficient conditions of the localization of the Fourier-Laplace series of distributions from liouville classes - Rakhimov, Abdumalik A.; Ahmedov, Anvarjon A.; Rasedee, hmad Fadly Nurullah (Institute of Physics Publishing (UK), 2013)
In this work we investigate the localization principle of the Fourier-Laplace series of the distribution. Here we prove the sufficient conditions of the localization of the Riesz means of the spectral expansions of the Laplace-Beltrami operator on the unit sphere.